Social Sustainability: Satisfying Owners and Communities by Multilevel Strategies of Contractors - Kittipos Kawesittisankhun; Jakrapong Pongpeng (My University, 2020)
In sustainable construction/production, the social dimension regarding owner and community satisfaction has received the least focus. To promote social sustainability, the multilevel strategies of contractors should be developed for owner and community satisfaction. However, a literature review shows that there are few studies on how multilevel strategies influence such satisfaction. Hence, this study aimed to analyze such influences. A survey was conducted to gather data from the Thai construction industry, and these data were then analyzed by a structural equation model (SEM). The results, for the first time, highlight that corporate strategy influences business strategy (direct influence = 0.98), which in turn influences functional strategy (direct influence = 0.93). Additionally, only functional strategy influences owner (direct influence = 0.84) and community satisfaction (direct influence = 0.66). Furthermore, parenting, cooperation, and equipment/machinery substrategies obtain the highest weights within the management levels of corporation, business, and function (regression weights = 0.49, 0.48, and 0.55), respectively. The work productivity and site organization indicators have the largest weights for owner and community satisfaction (regression weights = 0.47 and 0.57), respectively. The findings provide a guideline that helps contractors allocate their available resources to substrategies according to their regression weights, enhancing owner and community satisfaction.
Keywords: Corporation; Construction Project Management and Performance